The Effect of Good Corporate Governance, Sustainable Growth Rate on Disclosure of Sustainability Reporting and Moderated by Covid-19 - Lusmeida, Herlina; Adilla, Paskalis Krisna Putra Novaldi (Proceeding of International Conference on Entrepreneurship (IConEnt), 2023)
This study aims to determine the effect of Good Corporate Governance (“GCG”) and Sustainable Growth Rate (“SGR”) on Sustainability Reports (“SR”). GCG variables are measured using 15 indices that describe the overall GCG structure. Meanwhile, SGR is calculated using an analysis of the calculation of Return on Equity (ROE) minus the Dividend Payout Ratio. The research samples taken were companies engaged in manufacturing, mining, and industry which were listed on the Indonesia Stock Exchange (IDX). The data collected consists of secondary data taken from the period before COVID-19 (2018-2019) and the period during COVID-19 (2020-2021). The results that have been done show a significant effect between GCG and SR, SGR and SR, and the effect of COVID-19 on GCG on SR. while the effect of COVID-19 on SGR on SR did not have a significant effect. This study takes the renewal of the influence of GCG, SGR, on SR by measuring the influence of COVID-19 by taking companies that have an influence on the country's development. Good GCG and SGR can help disclose good SR with factors that have been taken into account against the tested line of business and coupled with the influence of COVID-19 making the Company show its commitment in providing good performance on factors that affect their daily operational work environment.